Proteomic studies of an explant model of equine articular cartilage in response to pro-inflammatory and anti-inflammatory stimuli - Williams, Adam (2014)
Osteoarthritis (OA) is characterised by cartilage degradation, inflammation and pain within synovial joints. OA is a major cause of morbidity in the elderly human population and in companion animals such as horses. Changes in expression and activity of pro-inflammatory cytokines, chemokines and catabolic mediators contribute towards OA progression, which can be studied using in vitro culture models and proteomic approaches. This project studied the secretome from an in vitro model of equine articular cartilage, aiming to develop understanding of cartilage biology and degradative processes. These studies also aimed to identify protein markers relevant to this explant model for screening anti-inflammatory properties of novel therapeutics. To evaluate responses to OA associated pro-inflammatory IL-1β and the non-steroidal anti-inflammatory drug (NSAID), carprofen, time courses of protein release were established in the explant model. The cartilage secretome contained cartilage extracellular matrix (ECM), non-ECM and intracellular proteins, all of which were identified by high-throughput mass spectrometry (MS). Semi-quantitative differences in protein release were reported between untreated control and IL-1β stimulated cartilage by MS. The release of glycosaminoglycans (GAGs) initiated by IL-1β was delayed when carprofen was present. The proteomic sample preparation method was adapted to deplete high abundance proteins that can hinder the detection of low level proteins in high-throughput MS analysis. Three depletion approaches were applied: CPC precipitation, concanavalin A lectin chromatography and Proteominer™ technology. These approaches provided additional identifications of the non-ECM secreted proteins MMP-10 and IL-9, and of additional intracellular proteins. Further optimization of these methods could further enhance the detection of low level proteins. Proteins identified by MS analysis of the cartilage secretome were assessed using quantitative western blotting analysis. Carprofen significantly reduced IL-1β stimulated release of MMP-1, MMP-3, MMP-13 and a fibronectin degradation product. Levels of clusterin were reduced by IL-1β and carprofen treatments. These specific proteins were shown to be markers of IL-1β stimulated inflammation and degradative processes, which can be significantly reduced by an anti-inflammatory such as carprofen. This thesis describes the use of proteomics with other approaches to study the effects of IL-1β and carprofen on release of several important structural, metabolic and inflammatory related components from cartilage. Carprofen was beneficial in decreasing certain aspects of inflammation and degradation, including significantly reducing release of MMPs and their catabolic products (fibronectin and GAGs) from the ECM. The equine explant model can be further studied with high-throughput MS to assess responses to various stimuli and detect released proteins. In conclusion, anti-degradative effects and MMP inhibition can be specifically monitored within this in vitro equine cartilage model, to screen efficacy of therapeutics and putative anti-inflammatories to relieve OA.